2016
DOI: 10.3390/fluids1040042
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Stresses and Hemolysis in Turbulent Flow Examined by Threshold Analysis

Abstract: Abstract:Use of laminar flow-derived power law models to predict hemolysis with turbulence remains problematical. Flows in a Couette viscometer and a capillary tube have been simulated to investigate various combinations of Reynolds and/or viscous stresses power law models for hemolysis prediction. A finite volume-based computational method provided Reynolds and viscous stresses so that the effects of area-averaged and time-averaged Reynolds stresses, as well as total, viscous, and wall shear on hemolysis pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(94 reference statements)
0
6
0
1
Order By: Relevance
“…2024 A common approach to consider turbulent effect on hemolysis is to formulate effective stress τeff using viscous stress together with Reynolds stress. 2528 However, it has been shown that the Reynolds stress is an inaccurate indicator of turbulent effects on hemolysis, 2933 and tends to overpredict the level of hemolysis. 24 Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…2024 A common approach to consider turbulent effect on hemolysis is to formulate effective stress τeff using viscous stress together with Reynolds stress. 2528 However, it has been shown that the Reynolds stress is an inaccurate indicator of turbulent effects on hemolysis, 2933 and tends to overpredict the level of hemolysis. 24 Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The power-law model established by Giersiepen et al (1990) has been considered in various studies as a fundamental model to estimate blood damage (Einav and Bluestein, 2004;Nobili et al, 2008;Wu et al, 2010;Wu et al, 2011). The limitation of this model is the requirement of empirically deriving the coefficients of the power law formulation for each prosthetic device (Ozturk et al, 2016), and their physical inconsistencies. The mathematical formula can be written as , where a, b, and c are constant values, is the acting shear stress, and is the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…** Increase of 20mg/dl in plasma Hb was considered as the threshold value for Kameneva, et al [122] study. *** This is the cumulative exposure time estimated by Ozturk, et al [125]…”
Section: Hemolysis Threshold In Laminar Viscous Shear Flowmentioning
confidence: 91%
“…114 The first issue with the Garon & Farinas [160] method is highlighted by the difference between Eqs. (127) and (125), which is that the difference between local velocity and the average velocity along the streamline that passes through the point is not included in Eq. (127).…”
Section: Transformation Of the Linearized Damage Functionmentioning
confidence: 99%